PLZ HELP ME IF YOU ARE A MR.BEAST FAN. The sum of 7 and 5 times a number is 48. What are the two numbers? What is the equation and the solution of the question.

Answers

Answer 1
Answer:

Answer:

I´m not a Mr. Beast fan but the answer is 4. 4*12 (which is the sum of 7 and 5) = 48

The equation is (7+5)x=48

Answer 2
Answer:

Answer:

i am a big fan here is the answer  (7+5)x=48

Step-by-step explanation:


Related Questions

Help me answer missing angles in each question please
Solve the following equation: 28 ÷ 7 + 2 × 3 = ?      A. 24B. 18C. 10D. 12
Where is the number 4 − 8 located on a horizontal number line?4 units to the left of 4 4 units to the right of 4 8 units to the left of 4 8 units to the right of 4
For which system of equations is (2, 2) a solution?a. –3x + 3y = 0 x + 6y = 10b. –2x + 5y = –6 4x – 2y = 4c. 5x – 2y = –6 3x – 4y = 2d. 2x + 3y = 10 4x + 5y = 18
Find the slope and​ y-intercept of the linex+2y=6

The base of a solid in the xy-plane is a circle with a radius of 3. cross sections of the solid perpendicular to the x-axis are squares. set up the integral to arrive at the volume of the solid and solve.

Answers

Answer:

\large \boxed{144}

Step-by-step explanation:

1. Set up the integral.

The equation for the circle is

x² + y² = 9

The bottom corners of the square are at  

(x, \sqrt{9 - x^(2)})\text{ and } (x, -\sqrt{9 - x^(2)})

The length (a) of a side is

a = 2\sqrt{9 - x^(2)}

and the area (A) of the square cross-section is

A = a² = 4(9 - x²)

The volume (V) of the solid is

V = \displaystyle \int_(-3)^(3) {4(9 - x^(2))} dx

2. Solve the integral

\displaystyle \int_(-3)^(3) {4(9 - x^(2))} dx = 4\begin{bmatrix}9x - (1)/(3)x^(3)\end{bmatrix}_(-3)^(3)= 4[(27 - 9) - (-27 +9)] = 4[18 - (-18)]\n= 4[18 + 18] = 4 *36 = \mathbf{144}\n\n\text{The volume of the solid is $\large \boxed{\mathbf{144}}$}

2x plus 4 in vertex form

Answers

Vertex form only applies to quadratics. A quadratic is a polynomial with 2 being the largest exponent. I don't see any x^2 term here. Please check the problem to make sure that it's typed correctly. 

Paula's time swimming in the Ironman Triathlon was 1 hour 25 minutes. Her time biking was 5 hours longer than her swimming time. She ran for 4 hours 50 minutes. How long did it take her to complete all three parts of the race? Use the model to help you organize your thinking.

Answers

Answer: 12 hrs 40 mins

Step-by-step explanation:

The swimming time was 1 hour 25 minutes.

Her biking time was 5 hours longer than the swimming time so it was:

= 1 hr 25 mins + 5 hours

= 6 hours 25 mins

Her running time was 4 hrs 50 mins.

Add them all up to find the amount of time ran. First add up the minutes:

= 25 + 25 +50

= 1 hr 40 minutes

Hours = 1 + 6 + 4

= 11 hours

Total:

= 11 + 1 hr 40

= 12 hrs 40 mins

Given: x + 3.8 > -10.02. Choose the solution set. a. {x | x ∈ R, x > -6.22} b. {x | x ∈ R, x > -10.40} c. {x | x ∈ R, x > -13.82}

Answers

x+3.8 \ \textgreater \  -10.02 \nx\ \textgreater \ -10.02 - 3.8 \nx\ \textgreater \ -13.82 \n \n\{ x | x \in \mathbb{R}, x\ \textgreater \ -13.82 \}

The answer is C.

What is the complete factorization of x2 + 2x − 63? A. (x + 21)(x − 3) B. (x − 9)(x + 7) C. (x + 9)(x − 7) D. (x − 21)(x + 3)

Answers

Answer:

(x + 9)(x - 7)

Step-by-step explanation:

We want to factorize x^2 + 2x - 63

We need to find two numbers such that their product is -63 and they add up to +2. The two numbers are +9 and -7:

x^2 + 9x - 7x - 63\n\n= x(x + 9) -7(x +9)\n\n = (x +9)(x -7)

The complete factorization is (x + 9)(x - 7)

The factored form of the expression x² + 2x - 63 is (x + 9)(x - 7).

What is the factored form of the expression?

Given the expression in the question:

x² + 2x - 63

To determine the complete factorization of the quadratic expression x² + 2x - 63, we aim to break it down into its simplest factors.

This is achieved through factoring, a process of identifying the expressions that, when multiplied, result in the original quadratic expression.

x² + 2x - 63

Now, find a pair of integers whose sum equals 2,

and whose product equals -63.

We use integers 9 and -7.

Next, rewrite the quadratic expression using these factors:

(x + 9)(x - 7)

Therefore, the complete factorization of x² + 2x - 63 is (x + 9)(x - 7).

Option C) (x + 9)(x - 7) is the correct answer.

Learn more about factorization here: brainly.com/question/20293447

#SPJ6

Which expression would represent the cost of one CD, if the total cost for three of them is $36?36-3
3(36)
36/3
3+36​

Answers

Answer:

C: 36/3

Step-by-step explanation:

36 ÷ 3 = 12

We solve by using the total amount of dollars and dividing by how many CDs there are

Answer:C: 36/3

Step-by-step explanation:

36 ÷ 3 = 12

We solve by using the total amount of dollars and dividing by how many CDs there are